2014
DOI: 10.1055/s-0034-1395678
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Aberrantly Spliced Transcripts of a Novel de novo GNAS Mutant in a Male with Albright Hereditary Osteodystrophy and PHP1A

Abstract: Pseudohypoparathyroidism (PHP) is a genetic disorder due to target-organ unresponsiveness to parathyroid hormone (PTH). PHP type 1A (PHP1A) is an autosomal dominant disease characterized by Albright hereditary osteodystrophy (AHO) and PTH resistance caused by defects at the GNAS locus. We analyzed the GNAS gene in a male with typical AHO and elevated PTH levels. We identified a novel de novo heterozygous mutation at the splice donor site in intron-7 (IVS7+1G>A, c.585+1G>A) of the GNAS gene. No GNAS mutations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In patients with PHP1A, the average level of TSH is 14.1 ± 10.3 mUI/1, with a range of 1.4 mUI/1 to 46.0 mUI/1 (REFS 24,30,38,67,98,100,117,119,122,123,129,144146,149,193205 ) A prompt diagnosis of hypothyroidism after birth and initiation of treatment does not seem to prevent the development of motor or cognitive delay 24 .…”
Section: Managementmentioning
confidence: 99%
“…In patients with PHP1A, the average level of TSH is 14.1 ± 10.3 mUI/1, with a range of 1.4 mUI/1 to 46.0 mUI/1 (REFS 24,30,38,67,98,100,117,119,122,123,129,144146,149,193205 ) A prompt diagnosis of hypothyroidism after birth and initiation of treatment does not seem to prevent the development of motor or cognitive delay 24 .…”
Section: Managementmentioning
confidence: 99%
“…Since then, several Gsa-coding mutations have been identified in all of its 13 exons with different frequency, with a detection rate of about 70% (33,34,35,36,37,38,39). Cases of deletions of 20q, including part or the whole GNAS gene, and an inversion at GNAS have been recently reported (40,41,42,43,44).…”
Section: Figurementioning
confidence: 99%
“…Some of the reported variants are located in the intronic regions near splicing sites. It was shown that these variants frequently lead to the preservation of the mutant intronic sequence in the mRNA [28,29]. In our case, we showed that the identified variant leads to the preservation of the intronic sequence containing a stop codon, which in turn leads to the truncated protein.…”
mentioning
confidence: 49%